Filter Implementation Using Output Transformer of UPS for Power Quality Improvement - Anandh N.; Pramod Antony D'Sa; M.V. Gautam; V.Sai Sandeep (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Power electronics play a significant role in different areas of technology, more usage of power electronic devices lead to more harmonic content and various power quality issues in the system.  Therefore, power quality gains more significance in the current era of research. Power electronics equipment’s with non-linear loads concludes with more harmonic disturbances and lower power factor. Harmonic impurities are the major problem ingredient due to the connection of non-linear load. To lessen the harmonics usually passive filters are used. The major objective of this work is to monitor and analyse the power quality of uninterrupted power supply by means of DAQ system that gathers real time data on the system and then the data is analysed using National Instruments LabVIEW. Once power quality analysis is done, a new technique of filter implementation using output transformer of the UPS was explored and passive filter was simulated using MATLAB/Simulink and then simulated filter was implemented in order to achieve power quality improvement.